The rapid development of thyroid lymphoma - case report - Kowalik, Marcin; Guz, Aleksandra; Myśliński, Wojciech; Mieczkowska, Jolanta (Journal of Education, Health and Sport, 2019)
Thyroid lymphoma is a rare malignant neoplasm of the thyroid gland, constituting about 5% of all cases of thyroid cancer. Its incidence is higher in female patients aged 60-70 years. Many affected patients have the history of Hashimoto disease. When the goitre increases and compression symptoms occur, quick diagnosis and treatment are required. The diagnosis is mainly based on histopathological examinations. Further treatment and prognosis depend on the histopathological subtype, progression and size of the tumour. Our case report describes a 70-year-old female patient who presented due to an increasing circumference of the neck and dyspnoea aggravating for three weeks. The course of disease and the patient's condition deteriorated rapidly. Based on clinical observations and histopathological findings, thyroid lymphoma was diagnosed.